2002
DOI: 10.1046/j.1537-2995.2002.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting bacteria in platelet concentrates by use of reagent strips

Abstract: Screening PC units by the reagent strip method resulted in 9.7 units per 1000 being wasted, but prevented two patients from receiving a PC unit containing B. cereus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 20 publications
1
32
2
1
Order By: Relevance
“…Higher WBC and also PLT content likely explains pH failure not due to bacterial contamination. In another study [8], thirty of the 3093 PC units was classified as positive by the reagent strips. Only two of 30 reagent strip screen positive units were also positive by the standard bacterial culture method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher WBC and also PLT content likely explains pH failure not due to bacterial contamination. In another study [8], thirty of the 3093 PC units was classified as positive by the reagent strips. Only two of 30 reagent strip screen positive units were also positive by the standard bacterial culture method.…”
Section: Discussionmentioning
confidence: 99%
“…They are based on changes in platelet unit strip pH and glucose that occurs following increasing levels of microbial contamination [6]. Overall sensitivity reported for the test was 95 % with a specificity of 98-100 % at 10 7 colony-forming units per milliliter (CFU/mL) [8]. The Bact/Alert system is cleared by FDA for quality control of bacterial culture in platelets.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…However, the overall sensitivity is only 10 6 to 10 7 CFU/ml (13,62,63,66). Werch et al, from the M. D. Anderson Cancer Center, reported on the screening of 3,093 platelet concentrates, in which they found that multireagent strips for 30 bags had glucose levels or pH outside of the reference range (63).…”
Section: Bacterial Detectionmentioning
confidence: 99%
“…6,30,[54][55][56][57] Of the initial 929 platelet concentrates that screened positively, 923 were not confirmed by subsequent culture, for a false-positive rate of 0.99%, which is very close to that previously reported using urine reagent strips (0.90%) and comparable to the rate for culture reported by AuBuchon et al 58 of 0.6%, but is nearly an order of magnitude higher than the false-positive rate reported for culture in other studies of 0.03% to 0.12%. 30,55,59 Variation in observed false-positive rates may be attributed to lack of standardization of the definition, with questionable distinction between "reactive signal" and "positive signal." Other contributing factors may include the actual contamination rate, differences in test sensitivities (detection threshold) between methods, and vagaries in sampling protocols between studies.…”
Section: Discussionmentioning
confidence: 99%